Eksplorasi Peta Interaktif untuk Mitigasi Bencana pada Siswa SMAS Wirabakti Gorontalo - Nurfaika, Nurfaika; Rusiyah, Rusiyah; Sabihi, Aprianto; Moko, Faisal; Mokodompit, Mohamad Alfarezy; Massi, Silva; Agu, Rahmad Rafly (-, 2025)
This community service activity aims to improve the competence of students of SMAS Wirabakti Gorontalo in utilizing digital map technology for disaster mitigation-based geography learning. Problems faced by partners include students' low understanding of spatial literacy, teachers' limitations in mastering mapping technology, and lack of infrastructure and collaborative support in schools. To answer these challenges, In-Service Training (IST) and On-Service Training (OST) training methods are used which integrate the use of Google Earth, InaRISK, and QGIS as learning media.This activity is carried out through three main stages: preparation, training, and evaluation. Evaluation was carried out through pre-test and post-test, response questionnaires, and observation of participant involvement. The results of the analysis showed an increase in students' average scores from 7.08 in the pre-test to 8.8 in the post-test. In addition, students demonstrate the ability to draw up risk maps and simple mitigation plans, as well as active involvement in practical sessions.This activity has proven to be effective in improving students' disaster literacy and geospatial skills and opening up new insights for teachers in learning innovation. Recommendations from these activities include further training for teachers, infrastructure improvements, and replication of programs in other schools. With this approach, it is hoped that a contextual, creative, and disaster-resilient learning environment will be created.